Effect of explosion source location on tunnel damage. Issue 4 (December 2020) - Prochazka, Petr; Jandeková, Dagmar
The experimental study, the results of which are presented in this article, focuses on the shock wave behavior in scale models of tunnel structures and their consequences on the damage of tubes simulating tunnel lining. The source of the explosion is located either on the longitudinal axis of the tunnel or it is located near the bottom of the tunnel. The second case is more akin to reality. This article analyzes the consequences of the location of explosion sources and the influence of their brisance. In order to compare the effects of explosions on the tunnel lining, the effect of the charge deposited on the axis of the tunnel is investigated on a 0.5-m-diameter tube, while the effect of the charge deposited outside the tunnel axis is monitored on a 1-m-diameter tube. Thus, the magnitudes of the brisance may be comparable for both cases. The characteristics of the shock waves are described. The mass of the charges is graded so as not to allow a total collapse of the structure, but to manifest its damage.